2015
DOI: 10.1038/cddis.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell imaging of inflammatory caspase dimerization reveals differential recruitment to inflammasomes

Abstract: The human inflammatory caspases, including caspase-1, -4, -5 and -12, are considered as key regulators of innate immunity protecting from sepsis and numerous inflammatory diseases. Caspase-1 is activated by proximity-induced dimerization following recruitment to inflammasomes but the roles of the remaining inflammatory caspases in inflammasome assembly are unclear. Here, we use caspase bimolecular fluorescence complementation to visualize the assembly of inflammasomes and dimerization of inflammatory caspases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…When we analyzed the appearance and localization of the fluorescent complexes produced by heme in each case, we noticed some differences ( Figure 2D). The caspase-1 complex appeared as a single green punctum typical of ASC specks and of ASC-induced caspase-1 BiFC that we previously reported (27,42). Caspase-4 and caspase-5 BiFC appeared as a series of punctate spots located throughout the cytoplasm of the cell that did not co-localize with mitochondria.…”
Section: Caspase-1 Caspase-4 and Caspase-5 Are Activated By Heme Inmentioning
confidence: 59%
See 3 more Smart Citations
“…When we analyzed the appearance and localization of the fluorescent complexes produced by heme in each case, we noticed some differences ( Figure 2D). The caspase-1 complex appeared as a single green punctum typical of ASC specks and of ASC-induced caspase-1 BiFC that we previously reported (27,42). Caspase-4 and caspase-5 BiFC appeared as a series of punctate spots located throughout the cytoplasm of the cell that did not co-localize with mitochondria.…”
Section: Caspase-1 Caspase-4 and Caspase-5 Are Activated By Heme Inmentioning
confidence: 59%
“…The pBiFC.VC155 and pBiFC.VN173 plasmids encoding C1-Pro, C4-Pro, or C5-Pro were described previously (27). Single mutations were introduced using QuikChange Site-Directed Mutagenesis Kit (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that while NLRC4 can recruit ASC and caspase‐1 to induce cytokine processing, it can also form as separate complex independent of caspase‐1 that induces cell death. We previously demonstrated that caspase‐4 or capase‐5 dimerization is induced upon NLRC4 overexpression . Thus, it is possible that pyroptosis induced by this logarithmic phase S. typhimurium assembles an NLRC4 inflammasome that recruits and activates caspase‐4 or caspase‐5 to induce pyroptosis.…”
Section: Inflammasomes: the Caspase‐1 Signaling Platformsmentioning
confidence: 98%